Testing Autoregressive Models Through the Example of Northern Hungary - Potvorszki, Gábor (Theory, Methodology, Practice – Review of Business and Management, 2012)
The aim of this study is to model regional economic performance by the application of autoregressive models for given variables. The Cobb-Douglas (CD) production function gives the basis, which is extended by the gross value added produced by the labour force. My hypothesis is that if the current income level as dependent variable is determined by those current independent variables according to the CD function then it can be assumed that the time lags of both the dependent and independent variables also have an influence on the current value of the dependent variable. I test this hypothesis through the example of Northern Hungary in the period 1995-2008.